2020
DOI: 10.1080/2578983x.2020.1727119
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and recidivism in relation to arrest: differentiating between partner violent perpetrator subtypes

Abstract: This study aimed to describe and compare arrested and non-arrested male intimate partner violence (IPV) perpetrators, in terms of individual characteristics and variables related to the IPV incident, in a sample of 628 perpetrators reported to the Swedish police. We also explored recidivism rates in relation to arrest within the total sample, as well as among subtypes of partner violent men (i.e. generally violent [GV] and partner only [PO] violent). The perpetrators in this longitudinal study were reported to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 43 publications
1
7
0
1
Order By: Relevance
“…That is, VAWA seems to have had a flattening effect where all IPV incidents receive similar treatment from the CJ system. This, in spite of evidence that there are some traits such as a lack of empathy and antisocial characteristics that are associated with more severe IPV incidents and recidivism (Petersson & Strand, 2020;Romero-Martinez et al, 2016). Chesney-Lind (2002) identified an emerging patters of racism once mandatory and pro-arrest laws were passed in the late 1980s.…”
Section: Ipv: the Familial Becomes Legalmentioning
confidence: 95%
See 1 more Smart Citation
“…That is, VAWA seems to have had a flattening effect where all IPV incidents receive similar treatment from the CJ system. This, in spite of evidence that there are some traits such as a lack of empathy and antisocial characteristics that are associated with more severe IPV incidents and recidivism (Petersson & Strand, 2020;Romero-Martinez et al, 2016). Chesney-Lind (2002) identified an emerging patters of racism once mandatory and pro-arrest laws were passed in the late 1980s.…”
Section: Ipv: the Familial Becomes Legalmentioning
confidence: 95%
“…These lawsuits helped to usher in a number of mandatory and pro-arrest laws across North America (Durfee & Fetzer, 2014; Fraehlich & Ursel, 2014), intended to mitigate the influence of police officer use of discretion in arrest. They have been met with mixed reactions as their deterring effect on recidivism has been shown to be moderate to minimal (Chesney-Lind, 2002; Petersson & Strand, 2020), while arrest rates for women who are arguably more often victims and survivors have increased (Chesney-Lind, 2002; Dichter, 2013; Fraehlich & Ursel, 2014). The increase in dual arrests that resulted from these laws have spurred intense debates among advocates regarding the blaming effect on survivors (Dichter, 2013), and raise additional concerns in relationships where children are placed in CW when both parents are arrested.…”
Section: Introductionmentioning
confidence: 99%
“…Discussions with the force illuminated a policy change in lockdown, to prioritise support for the most serious cases by limiting incidents recorded as medium-and high-risk. As physical abuse constituted a lower percentage of IPV incidents during lockdown, these changes in risk allocation may have been influenced by fewer injuries caused through direct physical violence because physical abuse incidents, especially those resulting in injuries, are often recorded as higher risk (Myhill, 2019;Petersson and Strand, 2020). The reduction in suspects' alcohol consumption may partially account for this decrease in incidents regarded as more serious, as alcohol consumption has been linked to increases in risks of IPV perpetration, physical aggression and victim injuries (Trujillo and Ross, 2008;Dichter et al, 2011).…”
Section: Changes In Distribution Of Da Risk Levelsmentioning
confidence: 99%
“…Table 3 demonstrates that arrest rate was significantly correlated with lockdown. Changes in frequencies and composition of DA risk levels recorded by the police could partially explain changes in arrest rates, as perpetrators whose abuse is rated as higher-risk are more likely to be arrested (Petersson and Strand, 2020). Indeed, chi-squared tests found that arrest frequency was significantly related to DA risk level for equivalent and lockdown datasets (X 2 (2, N = 5546) = 1458.58, p = <0.000 and X 2 (2, N = 5666) = 1997.97, p = <0.000 respectively).…”
Section: Arrestmentioning
confidence: 99%
“…However, little is known about the utility and applicability of IPVAW offender typologies in increasing the effectiveness of police and judicial work for the prevention of new IPVAW episodes. One of the few works that deals with this question is Petersson and Strand's (2020) longitudinal study (28-month mean follow-up period), which describes and compares 628 arrested and non-arrested male IPVAW perpetrators in Sweden, in terms of their individual characteristics (i.e., generally violent [GV] and partner only [PO] violent), and variables related to the IPVAW incident. Results showed that arrested perpetrators were more likely to be reported for severe forms of IPVAW, being assessed by the police postarrest with a higher recidivism risk, and being more likely to be prosecuted for the reported IPVAW incident.…”
Section: Introductionmentioning
confidence: 99%